Haemodynamic definitions and updated clinical classification of pulmonary hypertension. Issue 1 (24th January 2019) - Simonneau, Gérald; Montani, David; Celermajer, David S.; Denton, Christopher P.; Gatzoulis, Michael A.; Krowka, Michael; Williams, Paul G.; Souza, Rogerio
Since the 1st World Symposium on Pulmonary Hypertension (WSPH) in 1973, pulmonary hypertension (PH) has been arbitrarily defined as mean pulmonary arterial pressure (mPAP) ≥25 mmHg at rest, measured by right heart catheterisation. Recent data from normal subjects has shown that normal mPAP was 14.0±3.3 mmHg. Two standard deviations above this mean value would suggest mPAP >20 mmHg as above the upper limit of normal (above the 97.5th percentile). This definition is no longer arbitrary, but based on a scientific approach. However, this abnormal elevation of mPAP is not sufficient to define pulmonary vascular disease as it can be due to an increase in cardiac output or pulmonary arterial wedge pressure. Thus, this 6th WSPH Task Force proposes to include pulmonary vascular resistance ≥3 Wood Units in the definition of all forms of pre-capillary PH associated with mPAP >20 mmHg. Prospective trials are required to determine whether this PH population might benefit from specific management. Regarding clinical classification, the main Task Force changes were the inclusion in group 1 of a subgroup "pulmonary arterial hypertension (PAH) long-term responders to calcium channel blockers", due to the specific prognostic and management of these patients, and a subgroup "PAH with overt features of venous/capillaries (pulmonary veno-occlusive disease/pulmonary capillary haemangiomatosis) involvement", due to evidence suggesting a continuum between arterial, capillary and vein involvement in PAH. State of the art and research perspectives of haemodynamic definitions and clinical classification of pulmonary hypertension http://ow.ly/TJeR30mgWKj